The Type of Feedback Provided Can Affect Morphological Rule Learning of Young Children. Issue 4 (2nd October 2022) - Ferman, Sara; Shmuel, Sapir Amira; Zaltz, Yael
ABSTRACT: The acquisition of a new morphological rule can be influenced by numerous factors, including the type of feedback provided during learning. The present study aimed to test the effect of different feedback types on children's ability to learn and generalize an artificial morphological rule (AMR). Two groups of eight-year-olds learned to judge and produce repeated and new (generalization) items representing the AMR during ten training sessions. One group (n = 7) received only corrective feedback, that is, heard "the correct answer is … " after each incorrect answer, whereas the other group (n = 8) received corrective feedback following verification feedback, that is, heard "incorrect, the correct answer is … ." Performance in terms of accuracy and reaction times was compared to that of an additional eight-year-old group (n = 8) from a previous study who received only verification feedback, that is, heard "incorrect" following each incorrect answer. The data analysis that was conducted for all three groups (N = 23 total), with ten observations for each child revealed that corrective feedback improved implicit learning of the AMR and in some cases also allowed generalization to new items. The combination of verification and corrective feedback, however, yielded the best performance in generalizing the AMR, possibly by stimulating both implicit and explicit processes. These preliminary findings suggest that corrective feedback, and even more so combined corrective+verification feedback, can enhance procedural and declarative learning processes of young school-age children. Future studies may be necessary to test this inference in a larger group of school-age children, and across ages.